Impossibility in Modern Private Law - Aksoy, Hüseyin Can. author. aut Link
XIX, 200 p.
Keywords: This book provides an analysis of the treatment of impossibility in modern private law. The author explains the regulation of impossibility in German, Swiss and Turkish laws with a comparative analysis of the subject under (i) the United Nations Convention on International Sale of Goods (CISG), (ii) UNIDROIT Principles of International Commercial Contracts (PICC), (iii) Principles of European Contract Law (PECL also known as the Lando-Principles), (iv) Draft Common Frame of Reference (DCFR) and (iv) Common European Sales Law (CESL).